Effect of internal shading devices towards building energy efficiency in hot and humid climate - Nurafina, binti Safri (Universiti Malaysia Sarawak (UNIMAS), 2010)
Energy Efficiency is important to ensure our country's natural resources are adequate for future generation. Data in annual statistic from Malaysia Energy Commission shows that commercial buildings, such as an office building, are the second largest consumers of the electricity in this country. Transparent envelope of the building is determined to be the largest factors on cooling load placed on building's air conditioning system. The glazing area allows the admission of solar heat gain through radiation and conduction which causing the excessive usage of electricity by a chiller to keep to the set temperature in bUilding. Tabuan Height Commercial Centre was modeled in the simulation software and it was validated against the field measurement) rhe validated model was used to simulate various options of internal shading devices and their effect on building energy consumption. Results of this study show that internal shading devices do contribute as much as 31.3 percent of energy saving annually by controlling solar admission into the building.